2009
DOI: 10.1152/ajpgi.00074.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ano1 is a selective marker of interstitial cells of Cajal in the human and mouse gastrointestinal tract

Abstract: Populations of interstitial cells of Cajal (ICC) are altered in several gastrointestinal neuromuscular disorders. ICC are identified typically by ultrastructure and expression of Kit (CD117), a protein that is also expressed on mast cells. No other molecular marker currently exists to independently identify ICC. The expression of ANO1 (DOG1, TMEM16A), a Ca(2+)-activated Cl(-) channel, in gastrointestinal stromal tumors suggests it may be useful as an ICC marker. The aims of this study were therefore to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
341
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 337 publications
(373 citation statements)
references
References 42 publications
26
341
4
2
Order By: Relevance
“…ANO1 is robustly expressed in ICCs (Gomez‐Pinilla et al . 2009); moreover, electrical activity and contractility in the gastrointestinal tract have been severely compromised in ANO1 knockout mice (Huang et al . 2009; Hwang et al .…”
Section: Activation Of Ano‐mediated Caccs By Localized Ca2+ Signals Imentioning
confidence: 99%
“…ANO1 is robustly expressed in ICCs (Gomez‐Pinilla et al . 2009); moreover, electrical activity and contractility in the gastrointestinal tract have been severely compromised in ANO1 knockout mice (Huang et al . 2009; Hwang et al .…”
Section: Activation Of Ano‐mediated Caccs By Localized Ca2+ Signals Imentioning
confidence: 99%
“…Expression of DOG1 correlates with poor outcome in oesophageal squamous cell cancer [10][11][12]. Interstitial cells of Cajal (ICC) are another predominant site for Ano1 expression [13][14][15]. It has been reported that mice lacking Ano1 had fewer proliferating ICC [16].…”
Section: Introductionmentioning
confidence: 99%
“…2E). Recently, Zhu et al [13] suggested that Ca 2+ -activated Cl À conductance is involved in the pacemaking activity of ICCs, and another recent study confirmed that ICCs express ANO1 in the GI tract [14]. In addition, ANO1 was recently shown to function as a Ca 2+ -activated Cl À channel [15][16][17], and loss or block of ANO1 was found to block electrical slow waves in intact GI muscles [18].…”
Section: Resultsmentioning
confidence: 99%